Significant changes in gut microbiota and SCFAs among patients with newly diagnosed acute myeloid leukemia - An, Shujuan; Gong, Xia; Zhao, Long; Jian, Jinli; Guo, Yuancheng; Yang, Xiaoxiao; Sun, Hongjia; Li, Yang; Liu, Bei (Frontiers in Microbiology, 2025)
The purpose of this study was to identify whether the gut microbiota and metabolites of newly diagnosed acute myeloid leukemia (AML) patients displayed specific characteristic alterations and whether these changes could be used as potential biomarkers for predicting the disease. Notably, the gut microbiota and metabolites of AML patients exhibited significant structural and quantitative alterations at the time of their initial diagnosis. Beneficial bacteria, including Faecalibacterium, Collinsella, Lacticaseibacillus, and Roseburia, as well as butyric acid and acetic acid, were found to be considerably reduced in newly diagnosed AML patients. In contrast, Enterococcus and Lactobacillus, especially Enterococcus, were significantly enriched. Further investigation indicated that Enterococcus could serve as a potential intestinal marker, showing a strong negative correlation with the levels of acetic and butyric acid. Importantly, assays aimed at identifying AML demonstrated that Enterococcus, butyric acid, and acetatic acid exhibited excellent predictive effectiveness. Colonizing Enterococcus from patients were isolated for pathogen investigation, which revealed that these bacteria possess several strong virulence factors and multiple drug-resistance gene characteristics. Therefore, we speculate that the increase of Enterococcus may contribute to the development and progression of AML.